2019
DOI: 10.1007/s10796-019-09954-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards Increased Understanding of Open Data Use for Software Development

Abstract: The way open data resources of varied type and volume are used by software applications remains only partly known. In this study, following CRoss-Industry Standard Process for Data Mining, we propose a methodology for collecting and analyzing access data describing the use of open data resources by individual software applications. The methodology includes novel categorization of the data collected at an exposition portal providing access to underlying open data portals and third-party services. Furthermore, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Prior studies identified different PBRs and distinguished between application boundary resources, development boundary resources, and social boundary resources (Bianco et al, 2014;Petrik & Herzwurm, 2020a). Application boundary resources allow third-party applications to connect with the platform core, including APIs for accessing specific data (Grzenda & Legierski, 2021). Development boundary resources provide the means to developers to develop their applications, such as SDKs or debugging tools.…”
Section: Platform Boundary Resourcesmentioning
confidence: 99%
“…Prior studies identified different PBRs and distinguished between application boundary resources, development boundary resources, and social boundary resources (Bianco et al, 2014;Petrik & Herzwurm, 2020a). Application boundary resources allow third-party applications to connect with the platform core, including APIs for accessing specific data (Grzenda & Legierski, 2021). Development boundary resources provide the means to developers to develop their applications, such as SDKs or debugging tools.…”
Section: Platform Boundary Resourcesmentioning
confidence: 99%
“…In the application process with OGD, the government and society will be the beneficiaries, and more and more people have recognized that using OGD can promote business prosperity and social development (Kumar et al , 2021; Rumbold et al , 2020). In addition, open data competitions are gradually gaining widespread attention to better use the OGD and stimulate public participation (Grzenda and Legierski, 2021; Anderson Cook et al , 2019; Kitsios and Kamariotou, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital transformation towards a digital society requires education on digital literacy, which includes the usage, retrieval and sharing of information and the use of digital services, education and proactive involvement of citizens, who represent the feedback component of the ecosystem, ensuring improvement in the circular cycle. The need for data harmonization and standardized data quality evaluation on web portals, benchmarking frameworks [56], design requirements of portals, datasets and usage statistics [57], can lead to data improvement, and thus unlock the potential for new solutions from entrepreneurs [58] but also from universities [59]. As stated in [45], the EU supports the integration of data and knowledge to create online services and resources relevant for businesses and end-users using open data.…”
Section: Discussionmentioning
confidence: 99%